Reports to Independent Data Monitoring Committees: An Appeal for Clarity, Completeness, and Comprehensibility. (July 2018) - Buhr, Kevin A.; Downs, Matthew; Rhorer, Janelle; Bechhofer, Robin; Wittes, Janet
Background: Organizations presenting reports to independent data monitoring committees (IDMCs) should present data in a way that facilitates the ability of the IDMC to make informed judgments about the trial. Methods: This paper reviews reports to IDMCs and suggests approaches an independent statistical reporting group (ISRG) might take to prepare clear, complete, and comprehensible reports. Results: Sensible reporting by an ISRG and informed decision making by an IDMC require a productive partnership between the quantitative and clinical disciplines involved in a clinical trial. IDMC reports differ in structure and purpose from clinical study reports that summarize data at the end of a trial. The ISRG must have intellectual independence, recognizing that although the sponsor may be paying the bills, the ISRG is responsible to the IDMC. Ideally, it should have access to all data from the trial and should be capable of responding to requests from the IDMC without the sponsor's specific permission. The ISRG and sponsor must understand the differences between clean data at the end of the trial and data collected during the trial. To perform its role most effectively, the ISRG must collaborate with sponsor and IDMC clinicians to become conversant with the disease area, the product's mechanism of action, and the clinical relevance of important outcome measures. Conclusions: An IDMC is best served by an independent ISRG that will prepare clear, complete, and comprehensible reports. Given the complexities of interim data and IDMC requirements, the ISRG must be an active and informed participant in the monitoring process.